The endophytic fungi from wheat (Triticum aestivum L.) - Larrán, Silvina (2007)
In order to study the species composition of endophytes from wheat healthy plants in Buenos Aires Province (Argentina) and to determine their infection frequencies from leaves, stems, glumes and grains, wheat plants were collected from five cultivars at five growth stages from crop emergence to harvest. A total of 1,750 plant segments (leaves, stems, glumes and grains) were processed from the five wheat cultivars at five growth stages, and 722 isolates of endophytic fungi recovered were identified as 30 fungal genera. Alternaria alternata, Cladosporium herbarum, Epicoccum nigrum, Cryptococcus sp., Rhodotorula rubra, Penicillium sp. and Fusarium graminearum were the fungi that showed the highest colonization frequency (CF%) in all the tissues and organs analysed. The number of taxa isolated was greater in the leaves than those in the other organs analysed.